2020
DOI: 10.1002/pen.25426
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced (thermo)mechanical properties in biobased poly(llactide)/poly(amide‐12) blends using high shear extrusion processing without compatibilizers

Abstract: Compatible and partly‐biobased poly(l‐lactide) (PLA)/polyamide‐12 (PA12) blends (30 wt% PA12) are here processed by twin‐screw extrusion at high shear without added compatibilizers and the effect of several processing parameters (screw speed, feed rate) on final properties (tensile strength, ductility, impact toughness, thermal resistance) is addressed. High tensile strengths could be maintained for these blends with a maximal ductility (225%) and impact toughness (48 kJ/m2) achieved for an optimal screw speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Its enhanced toughness properties and its ability to widely extend before it breaks are some of its merits for utilization in 3D printing [ 11 , 13 , 29 , 38 ], while its flow behavior is trouble-free for both the extrusion and the 3D printing process [ 37 ]. Additionally, it has very good behavior when mixed with additives for the improvement of its properties [ 38 , 55 ]. Finally, its performance does not seem to degrade even after five (5) recycling loops [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its enhanced toughness properties and its ability to widely extend before it breaks are some of its merits for utilization in 3D printing [ 11 , 13 , 29 , 38 ], while its flow behavior is trouble-free for both the extrusion and the 3D printing process [ 37 ]. Additionally, it has very good behavior when mixed with additives for the improvement of its properties [ 38 , 55 ]. Finally, its performance does not seem to degrade even after five (5) recycling loops [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high speed shear processing technology, which is used to improve the compatibility of incompatible blends, polymer/filler, blend/filler systems by applying high shear stress and blending only by adjusting the screw speed (above 1000 rpm). In recent years, ultra-high speed shearing has been reported for biodegradable polymer blends such as PLA/polyamide 12 (PA12) 59 and PLA/ olefin block copolymer (OBC)/ethylene glycidyl methacrylate (EGMA) 60 . It has been found that ultra-high speed shearing can improve the blend morphology and affect the final mechanical properties of the products.…”
Section: Other Processing Techniquesmentioning
confidence: 99%
“…At present, the main research works carried out by scholars in this field are introduced as below (Figure 1). 32,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]…”
mentioning
confidence: 99%
“…For AM technologies, the reported disadvantages are mainly related to poor fusion [13,20] and anisotropic behavior [8], which is usually due to layer-by-layer adhesion quality issues. To improve the performance of the 3D-printed parts, much research has been conducted regarding the selection of 3D printing parameters [21], such as layer height [20][21][22][23][24], extrusion temperature [22][23][24][25][26], infill pattern [4,27] and ratio, etc. Another way to improve such anisotropy in mechanical and other properties is to create new composite materials [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%